Experimental investigation for combustion performance of hydrogen and natural gas fuel blends - Sorgulu, Fatih; Ozturk, Merve; Javani, Nader; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
The current study aims to investigate the effect of adding hydrogen into natural gas. Some significant parameters, such as natural gas consumption, heating time and heating value, are studied experimentally to observe the effects of hydrogen addition into natural gas on these parameters. Natural gas combustion in a gas stove is compared with the burning of hydrogen and natural gas blend in three different hydrogen volumetric fractions of 10%, 20%, and 30%. In order to minimize the errors in the experiments, the heating period is prolonged by using 5 kg of tap water heated from the ambient temperature to 60 degrees C. Two gas stoves are used for natural gas and hydrogen-natural gas blend simultaneously and under the same operating conditions. Tests are repeated and values are checked through an error analysis process. 0.045 m3 of natural gas and 0.011 m3 of hydrogen in the blend (with a hydrogen ratio of 20%) are consumed for the same heating load requirement. The results of this study show that 8% of the natural gas can be saved once hydrogen is added to natural gas in a 20% blend. Meanwhile, there is a 15.9% increase in heating time for the 20% volumetric hydrogen in the blend.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Natural gas; Blend; Combustion; Heating value; Efficiency; SCENARIOS; Chemistry; Electrochemistry; Energy & Fuels